(untitled) - Ray, Oakley (Boston, MA., 2002)
Designed for the introduction to drugs and substance abuse course as taught in departments of health education, psychology, biology, sociology, and criminal justice, this full-color market-leading text provides the latest information on drugs and their effects on society and human behavior. For over thirty years, instructors and students have relied on it to examine drugs and behavior from the behavioral, pharmacological, historical, social, legal, and clinical perspectives.
Keywords: Drugs of abuse,Neuropsychopharmacology; Social aspects